Does preeclampsia impact the gut microbiota of preterm offspring during early infancy? - Yang Chen; Zhou-Ting Yi; Hai-Long Yu; Xiao-Yan Wu; Jun-Ping Wang; Chuan Nie; Hui Li; Sheng-Hui Li; Qiu-Long Yan; Tian-Wen He; Min-Chai Chen; Xin-Yue Yang; et al. (Journal of Translational Medicine)
Abstract Preeclampsia (PE) is a pregnancy complication characterized by high blood pressure and organ damage. This study investigates the differences in the gut microbiota between preterm neonates born to mothers with PE and those born to mothers without PE (PR), aiming to understand how maternal health conditions like PE influence neonatal gut microbiota. The early gut microbiota plays a crucial role in neonatal health, and disturbances in its development can have long-term consequences. Fecal samples were collected from preterm neonates of PE and PR mothers at 2 and 6 weeks postpartum and analyzed using shotgun metagenomic sequencing. We found that PE significantly affected the gut microbial composition of preterm neonates, particularly at 2 weeks postpartum. The gut microbial diversity in the PE_2 group was notably lower compared to the PR_2 group, with no significant difference observed between the PR_6 and PE_6 groups. At the phylum level, Firmicutes and Proteobacteria were predominant, with significant differences observed, particularly a lower abundance of Actinobacteria in the PE_2 group. At the genus level, Escherichia, Enterococcus, and Klebsiella were more prevalent in the PE_2 group, whereas Bifidobacterium and Cutibacterium dominated the PR_2 group. The gut virome analysis showed no significant differences among the groups. Functional analysis revealed distinct metabolic pathway activities across the groups, suggesting that early disturbances due to PE impact the establishment of healthy gut microbiota. These findings underscore the substantial influence of maternal health on the early development of the neonatal gut microbiota and highlight the potential long-term health consequences. Additionally, the differences in metabolic pathways further emphasize the impact of preeclampsia on gut microbiota functionality.